Role of cervical length assessment at mid-trimester scan for predicting preterm births: An experience from Tertiary Hospital - Tamrakar, Suman Raj; Shrestha, Rubina (Journal of Kathmandu Medical College, 2020)
Background: Ultrasound has revolutionized the pattern of care and management. Mid trimester ultrasound (transabdominal) is a valuable method for pregnant clients to predict preterm births.Objectives: To assess cervical length at 20 to 24 weeks obstetric scan for predicting risk of preterm delivery and to determine the sensitivity and specificity of assessing cervical length as a predictor of preterm delivery.Methodology: This is a prospective study conducted at a Tertiary Hospital. Pregnant clients with singleton pregnancy at 20 to 24 weeks were enrolled for transabdominal ultrasound for assessing cervical length as a predictor of preterm delivery.Results: Of 1027 pregnant clients screened, the mean age was 22.92±3.45. Mean gestational age during scan was 21+5 weeks of gestation. About 2.43% of clients were found to have short cervix < 2.5 cm with mean cervical length 3.8 cm. The risk of preterm delivery was almost two fold when cervical length was < 2.5 cm. The sensitivity, specificity, positive predictive value and negative predictive value to predict preterm delivery were 32%, 85.9%, 5.44% and 98.04% respectively.Conclusion: Assessment of the cervical length at mid-trimester can be useful tool for predicting risk of preterm delivery.